Mudas de Timburi e Chico-magro submetidas à omissão de macronutrientes - Oliveira, Douglas Póvoas de (2012)
This work aimed to evaluate the effect of macronutrient omission on the morphology, the dry mass production, the accumulation of nutrients, as well as identifying visual symptoms in seedlings Timburi (Enterolobium contortisiliquum) and Chico-magro (Guazuma ulmifolia). The seedlings were grown in sand and when they reach about 20 cm were transferred to PVC tubes filled with sand. At 30 days, so the seedlings subjected to complete nutrient solution for adaptation, by renewing the solution every five days After this period the seedlings were subjected to seven treatments (full, and the omission of N, P, K, Ca, Mg and S) and three replications in a completely randomized design. The solutions were renewed every five days. Every 30 days were recorded height, stem diameter, and deficiency symptoms were identified and photographed every 15 days. After this period the seedlings were oven dried, weighed, ground and macronutrients were quantified. The results were submitted to ANOVA and means were subjected to Dunnett's Test at 5%. To Timburi the height and the dry matter production were higher with the omission of K, the diameter of the cervix were higher with the omission of P, Ca, Mg and S, the highest levels of macronutrients are N, Ca and Mg in shoots and K and S in the root. For the Chico-thin height, stem diameter and dry mass were lower with the omission of N, the highest levels of macronutrients in the shoots were N, S and Mg, and at the root the Ca.